Foraging mode, relative prey size and diet breadth: A phylogenetically explicit analysis of snake feeding ecology. Issue 5 (22nd March 2019) - Glaudas, Xavier; Glennon, Kelsey L.; Martins, Marcio; Luiselli, Luca; Fearn, Simon; Trembath, Dane F.; Jelić, Dušan; Alexander, Graham J.
Abstract: Foraging modes (ambush vs. active foraging) are often correlated with a suite of morphological, physiological, behavioural and ecological traits known as the "adaptive syndrome" or "syndrome hypothesis." In snakes, an ecological correlate often reported in the literature is that ambush‐hunting snakes have a higher relative meal size compared to actively foraging snakes which feed on smaller prey items. This "large meal versus small meal" feeding hypothesis between ambush and active foragers has become a widely accepted paradigm of snake feeding ecology, despite the fact that no rigorous meta‐analysis has been conducted to support this generalization. We conducted a phylogenetically explicit meta‐analysis, which included ca. 100 species, to test this paradigm of snake feeding ecology. We gathered data on prey size by inducing regurgitation by palpation in free‐ranging snakes and by examining the stomach contents of preserved museum specimens. When we found prey, we recorded both snake and prey mass to estimate relative prey mass (prey mass/snake mass). We also reviewed published studies of snake feeding ecology to gather similar information for other species. Ambush and active foragers did not differ in minimum or average meal size but the maximum meal sizes consumed by ambush‐foraging snakes were larger than the maximum meal sizes eaten by active foragers. This results in ambush‐foraging snakes consuming a significantly wider range of meal sizes, rather than being large meal specialists compared to active foragers. We argue that ambush foragers evolved to be more opportunistic predators because they encounter prey less frequently compared to active foragers. This hypothesis is further supported by the fact that ambush foragers also exhibited marginally wider diet breadths, consuming a broader range of prey types in comparison with active foragers. Our study challenges aspects of the foraging syndrome as it is currently conceived, and our results have important implications for our understanding of how foraging mode has shaped the behaviour and physiology of ambush‐foraging snakes. Abstract : Ambush‐foraging snakes are generally assumed to specialize on relatively larger prey compared to active foragers. This study shows that, rather than being large meal specialists, ambush‐foraging snakes consume a significantly wider range of meals sizes in comparison with active foragers.